Retentive drug delivery systems based on shape memory materials. Issue 25 (20th December 2019) - Maroni, Alessandra; Melocchi, Alice; Zema, Lucia; Foppoli, Anastasia; Gazzaniga, Andrea
ABSTRACT: Retentive drug delivery systems are intended for prolonged residence and release inside hollow organs of the body, in pursuit of either local or systemic therapeutic goals. Because of the relatively long‐lasting period of time they could cover during operation, a primary advantage arising from their use would lie in reduced dosing frequency, thereby improving the overall adherence of patients to prescribed medication regimens. The treatment of numerous pathologies that affect the urinary bladder and the stomach could especially benefit from viability of such delivery technologies. Moreover, by making use of effective gastroretentive dosage forms, the bioavailability of drugs that are preferably absorbed from the upper gastrointestinal tract could be increased. Expansion of devices following administration is often exploited for retention purposes, and several formulation strategies have been proposed in this respect. Innovative applications of shape memory materials have also been explored, highlighting the great inherent potential for facing the challenges involved. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48798. Abstract :